Using Pollen Records from New Zealand and Southern Chile to Reconstruct New Zealand Climate Variability over the Last 14,000 years - Jara Parra, Ignacio Alonso (11710115) (2016)
Climate variability in New Zealand (34-47°S), a long, narrow continental strip straddling the mid-latitudes of the Southern Hemisphere, results largely from the interplay between sub-tropical and sub-Antarctic atmospheric and oceanic circulation systems. Despite their importance to present-day New Zealand climate, these hemispheric-wide systems have only recently come under the spotlight of paleo-climate investigations with most attention having traditionally been centred on reconstructing climate trends. This PhD adopts a broader approach to climate reconstruction, by developing and comparing two new pollen-climate reconstructions from New Zealand (38-42°S) and one from Patagonia, Southern Chile (43°S). At each site, paleo-climate interpretations are based on the changes in climate-sensitive plant indicators. The influence of hemispheric atmospheric circulation on New Zealand climate history is assessed by: (1) comparing New Zealand climate/vegetation trends with published proxies from low- and high-latitudes, and (2) comparing New Zealand reconstructions with the Patagonian record. Finally, a multi-millennial pattern of Southern Hemisphere circulation over the last 14,000 cal yr BP (calendar years before AD 1950) is outlined. The first record presented is a 16,000-year temperature reconstruction from a small alpine lake in South Island, New Zealand (41°S), based on pollen and plant macrofossils. Climate variations are interpreted from the relative abundance of lowland and highland vegetation. The results include a lifting of the altitudinal forest limits attributed to warming pulses between 13,000-10,000 cal yr BP and between 7000-6000 cal yr BP, and a decline of lowland relative to upland forest taxa interpreted as cooling trends between 10,000-7000 cal yr BP and over the last 3000 years. The second record gives 15,000-year temperature and precipitation reconstructions from a peatbog in northern New Zealand (38°S), based on pollen and charcoal analysis. Temperature changes are assessed based on two quantitate reconstructions, whereas precipitation trends are inferred from variations in arboreal taxa with different drought tolerances. A long-term warming is inferred between 14,600-10,000 cal yr BP. Persistent dry conditions are recorded between 12,000-10,000 cal yr BP, followed by a long-term wet period between 10,000-6000 cal yr BP. The last 7000 years feature a long-term drying trend that culminates with persistent drier conditions over the last 3000 years. The third record provides a 16,000-year reconstruction from a small lake in Northwestern Patagonia (43°S), based on pollen and charcoal analysis. Climate conditions are inferred from the relative variations of pollen types with distinctive climate tolerances and complemented with changes in fire activity. These variations are in turn interpreted as resulting from changes in the position and/or strength of the Southern Westerly Winds (SWW). Cold and moist conditions attributable to stronger/northward-shifted SWW winds are observed between 16,000-13,600 cal yr BP. In contrast, warm and dry conditions suggestive of weaker/southward-shifted SWW are detected between 12,000-10,000 cal yr BP. The last 6000 years shows a trend towards colder conditions and increasing precipitation variability, suggesting a highly variable westerly flow over Patagonia. A comparison between the New Zealand and the Patagonia records suggest: (1) weakened/southward-shifted westerly flow over the southern mid-latitudes between 13,000-10,000 cal yr BP caused rapid warming and peak temperatures in New Zealand, as well as dry conditions in Northern New Zealand, (2) Enhanced/northward-shifted SWW over the southern mid-latitudes between 9000-4000 cal yr BP caused decreasing temperatures in the South Island and increasing precipitation in Northern New Zealand and (3) Overall weakened/southward-shifted SWW after 4000 cal yr BP caused a decrease in temperature in the southern New Zealand site. Drier conditions in Northern New Zealand and the overall increase in climate instability at all sites may have resulted from more frequent El Niño events along with an increase in sub-tropical climate variability.